Решите уравнения :
1) 2x (3 + 8x) - (4x - 3) (4x + 3) = 1,5x
2) ( x - 1) ( x + 2) = 2 ( x - 5 )² - x ( x - 3)
3)( 6x - 7)² - 5 (2x - 5) (2x +5) - 2 (4x - 15) (2x - 4) = -2
Ответы
1) 2х(3+8х)-(4х-3)*(4х+3)= 1,5х 6х+16х^2-(16x^2+12x-12x-9)=1,5х 6х+16х^2-16x^2 +12x-12x+9=1,5х 6x+9=1,5х 6х-1,5х=-9 4,5х=-9 х=-9:4,5 х=-2 16x^2 --это как х в квадрате. 2)(x-1)*(x+2)=2*(x-5)^2-X*(x-3) X^2+2X-X-2=2*(X^2-10X+25)-X^2+3X X^2+2X-X-2=2X^2-20X+50-X^2+3X X^2-2X^2+X^2+2X-X+20X-3X=50+2 2X^2-2X^2+18X=52 18X=52 X=52:18 X=2,888888889 примерно 3